RECESSED BALCONY HEAT RE-ENTRY EFFECT ON FAÇADE WITH CONDENSER UNITS - Kevin Yonathan Tanumidjaja; Danny Santoso Mintorogo; Rully Damayanti (DIMENSI (Journal of Architecture and Built Environment), 2021)
The use of split-type air conditioner in Surabaya results in the almost universal typical apartment layouts which feature a recessed balcony upon the building’s exterior façade which then utilized as air-conditioner condenser unit storage. Façade geometry with recessed balcony itself carries its own characteristic of surface air movement which affects the general Indoor Air Quality (IAQ) and heat dissipation of a building. Nevertheless, façade as architectural elements greatly influence building’s energy performance. Inefficiencies in heat dissipation from a condenser unit is detrimental on its performance and precipitate energy wastage. Based on computational fluid dynamics (CFD) analysis incorporated with energy performance evaluation, the effectiveness of façade geometry with recessed balcony is explored in this paper. It was found that recessed balconies are not an ideal place for condenser unit placement on a façade where many factors contributed to promoting heat re-entry from condenser units into the building’s interior.